2013
DOI: 10.1210/jc.2012-3532
|View full text |Cite
|
Sign up to set email alerts
|

Dipeptidyl Peptidase IV Inhibition Does Not Adversely Affect Immune or Virological Status in HIV Infected Men And Women: A Pilot Safety Study

Abstract: Despite lowering SDF1α levels, sitagliptin did not adversely affect immune or virological status, or increase immune activation, but did improve glycemia in healthy, nondiabetic HIV-positive adults. These safety data allow future efficacy studies of sitagliptin in HIV-positive people with cardiometabolic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…However, in our participants, SDF‐1α levels were rather decreased by vildagliptin (Table ). In the case of non‐diabetic HIV‐positive patients, sitagliptin treatment up to 24 weeks also decreased serum SDF‐1a levels compared with a placebo. More recently, Aso et al .…”
Section: Discussionmentioning
confidence: 96%
“…However, in our participants, SDF‐1α levels were rather decreased by vildagliptin (Table ). In the case of non‐diabetic HIV‐positive patients, sitagliptin treatment up to 24 weeks also decreased serum SDF‐1a levels compared with a placebo. More recently, Aso et al .…”
Section: Discussionmentioning
confidence: 96%
“…Previously, we found that sitagliptin (100 mg/d, 16 -24 wk) did not adversely affect virological or immune status in cART-treated HIVϩ adults with normal glucose tolerance (21). Whether sitagliptin reduces inflammation and immune cell activation in HIVϩ adults with impaired glucose tolerance (IGT) is unknown.…”
mentioning
confidence: 99%
“…Whereas the majority of successful antipsoriatic medications are immunosuppressive, none of the hypoglycemic agents show evidence of suppression of the immune system [78][79][80][81] . These medications are frequently used in the diabetic population without complication, and the side effects are well tolerated.…”
Section: Resultsmentioning
confidence: 99%
“…An earlier consultation from endocrinology may be beneficial. Hypoglycemic agents are commonly used, safe, well tolerated, and are unlikely to be immunosuppressive [78][79][80][81] . For patients in which immunosuppression is contraindicated, off-label usage of hypoglycemic agents may be warranted to control severe psoriasis and improve quality of life while avoiding the toxic effects of other systemic therapies.…”
Section: Resultsmentioning
confidence: 99%